2016
DOI: 10.1021/acs.biochem.6b00043
|View full text |Cite
|
Sign up to set email alerts
|

Substrate Binding Mode and Molecular Basis of a Specificity Switch in Oxalate Decarboxylase

Abstract: Oxalate decarboxylase (OxDC) catalyzes the conversion of oxalate into formate and carbon dioxide in a remarkable reaction that requires manganese and dioxygen. Previous studies have shown that replacing an active-site loop segment Ser161-Glu162-Asn163-Ser164 in the N-terminal domain of OxDC with the cognate residues Asp161-Ala162-Ser-163-Asn164 of an evolutionarily related, Mn-dependent oxalate oxidase gives a chimeric variant (DASN) that exhibits significantly increased oxidase activity. The mechanistic basis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
35
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(39 citation statements)
references
References 46 publications
4
35
0
Order By: Relevance
“…A similar mode of substrate binding, where oxalate binds in an end-on conformation providing an empty coordination site for dioxygen ligand was observed in oxalate decarboxylase. 69 …”
Section: Enzymes Structurally and Functionally Similar To Ardmentioning
confidence: 99%
“…A similar mode of substrate binding, where oxalate binds in an end-on conformation providing an empty coordination site for dioxygen ligand was observed in oxalate decarboxylase. 69 …”
Section: Enzymes Structurally and Functionally Similar To Ardmentioning
confidence: 99%
“…Yet, the presence of dioxygen is obligatory for catalysis and O2 is generally considered to act as a co-catalyst (6). Several crystal structures of the enzyme have appeared in the literature over the past 16 years all of which refer to enzyme poised at a pH of 7.5 or higher (7)(8)(9)(10)(11)(12)(13)(14). Yet, OxDC is only active at low pH with peak activity at or below pH4 and negligible activity above pH7 (15).…”
Section: Introductionmentioning
confidence: 99%
“…Using a series of lid mutants, Burrell et al concluded that E162 is essential for decarboxylase activity and suggested that it acts as the transient base that picks up the acidic proton from the oxalate monoanion during an initial PCET step (10). E162 turns inward toward the N-terminal Mn as seen in the closed-loop crystal structure by Just et al (8) However, this conformation is unlikely to be the catalytically active one since it presents a steric clash with substrate bound to Mn (13). Saylor et al reported on the structure of the T165V mutant enzyme which showed carbonate (or bicarbonate, a competitive inhibitor (20)) bound in the active site (11).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations